A New Block S-Random Interleaver for Shorter Length Frames for Turbo Codes - Mohammad Salim; R.P. Yadav; Kapil Narwal; Aarti Sharma (Bulletin of Electrical Engineering and Informatics, 2013)
In this paper, we have proposed a new design of interleaver based on S-random and block interleaver. The characteristics of both block and S-random interleaver are used by this proposed interleaver.  There is a large influence of free distance in turbo codes due to interleaving as it lowers the error floor. The free distance of turbo codes can be increased by designing interleaver with high spread. In this case, the overall spreading factor is increased significantly for smaller length frames also. The simulations results are compared with full S-random interleavers. The bit error rate performance of proposed interleaver for Turbo codes is much better than full s-random interleaver at the cost of small delay.